Polypharmacy and potential drug–drug interactions among Greenland’s care home residents - Albertsen, Nadja; Sommer, Tine Gjedde; Olsen, Thomas Mikkel; Prischl, Anna; Kallerup, Hans; Andersen, Stig (Therapeutic Advances in Drug Safety, 2022)
Background: As lifetime expectancy in Greenland is steadily increasing, so is the proportion of elderly Greenlanders. Old age is associated with polypharmacy, and in this study, we aim to describe the prevalence and characteristics of polypharmacy among the care home residents in Greenland. Methods: Eight care homes in Greenland were visited between 2010 and 2016. Questionnaires including information on prescribed medication and comorbidities were collected and analyzed. Drugs were categorized according to Anatomical Therapeutic Chemical (ATC) category, and potential drug–drug interactions (pDDIs) were assessed using the Danish Interaction Database. Polypharmacy was defined as five or more prescribed drugs. Results: All 244 eligible residents were included in the study. The median number of prescribed drugs per resident was six, and women were prescribed more drugs than men (median six versus five). More than 60% of all residents fulfilled the criteria for polypharmacy. The residents in the polypharmacy group had a higher body mass index (26.9 versus 24.3) and more chronic diseases (median two versus one), and more often pulmonary (14% versus 1%) or endocrine disease (22% versus 2%) than in the non-polypharmacy group. The most prescribed drugs belonged to ATC category N (nervous system, 78% of the residents). Finally, pDDIs were found among 61% of the residents and were more common in the capital (77%), which also had the highest proportion of residents with polypharmacy (77%). Conclusion: This is the first study to describe the patterns of polypharmacy and pDDIs among the elderly in care homes in Greenland. Our findings indicate that polypharmacy is as common in Greenland as elsewhere in the Western world, but there are local differences in the prevalence. Plain Language Summary: Polypharmacy among the elderly in care homes in Greenland The lifetime expectancy of the Greenlandic population is increasing, and so is the number of elderly Greenlanders. Previous studies have shown that the elderly have a higher ...